Driver acceptance of new technology : theory, measurement and optimisation - Regan, Michael A.; Horberry, Tim; Stevens, A. (Researcher in transportation) (Human factors in road and rail transport, 2014)
"Acceptance of new technology and systems by drivers is an important area of concern to governments, automotive manufacturers and equipment suppliers, especially technology that has significant potential to enhance safety. To be acceptable, new technology must be useful and satisfying to use. If not, drivers will not want to have it, in which case it will never achieve the intended safety benefit. Even if they have the technology, drivers may not use it if it is deemed unacceptable, or may not use it in the manner intended by the designer. At worst, they may seek to disable it"-Provided by publisher.